Injustiças socioambientais perpetradas em Aurizona (MA): uma análise à luz do Acordo de Escazú - ALENCAR, Sahid Sekeff Simão (2020)
The present research approaches socio-environmental injustices against the most vulnerable communities living around Mineração Aurizona, located in Godofredo Viana - Maranhão (Brazil), more specifically in one of its districts. The approach is based on a threefold aspect extracted from the Escazú Agreement: access to information, public participation and access to socio-environmental justice. In this context, the problem faced is whether, given the guarantee of an ecologically balanced environment (provided for in the Federal Constitution of 1988), and the parameters of the Escazú Agreement, in clear harmony with the realization of a socio-environmental democracy, the holders of the potentially affected rights have obtained access to adequate, sufficient and previously available information, as well as to socio-environmental justice, and have participated in decision-making regarding the social, economic and environmental effects generated by the extraction and processing of gold in the region. To this end, using the theoretical substrate developed by Ulrich Beck and Anthony Giddens, the main objective is to defend an intertwining of environmental weaknesses, human rights violations and risk society. The investigation is guided by a legal-sociological theoretical-methodological approach, anchored on a self-sufficient vision of Law and promoting interdisciplinarity with environmental sociology. As for the methodological path, a qualitative and quantitative approach is adopted, articulated by inductive reasoning, and data gathering procedures by means of semi-structured interviews with local residents. In addition to the bibliographic research carried out in specialized journals, the collected data are analyzed by the content analysis technique, in the terms formulated by Laurence Bardin. In a complementary sense, ongoing or already concluded judicial demands, proposed in the competent cour of the city of Godofredo Viana are analyzed. In one of the centers of these demands was Mineração Aurizona. As a result of the interviews, a violation of human rights was evaluated as a corollary of the disregard for access to information, which is a fundamental and instrumental right, as well as the persistence of artificial risk management and the bilaterality in making environmental decisions between entrepreneurs and the State, without the proper opening of social risk definition processes. It is concluded that the greater permissiveness regarding the inspection of effective environmental impacts and disrespect for the human rights of the population of Godofredo Viana, a city financially dependent on mining, is a constant in Brazil, whether due to the prioritization of economic advances obtained through mining or to the inadequate measurement of latent side effects on the most vulnerable.